2022
DOI: 10.1002/lol2.10277
|View full text |Cite
|
Sign up to set email alerts
|

Widespread variation in salt tolerance within freshwater zooplankton species reduces the predictability of community‐level salt tolerance

Abstract: Not all populations of a species have the same sensitivity to contaminants, yet no studies have assessed this variation for multiple species across large geographic regions. Our study is the first to quantify within-species variation in salt tolerance (chloride, Cl À ) by conducting experiments at 16 environmentally diverse locations and compiling published tolerances from laboratory studies. Across our study sites, we found that Cl À sensitivity varied up to 4.2x AE 3.0 SD within species. This variation was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Vitally, Hébert et al (2022) showed that the loss in abundance was accompanied by a loss in zooplankton biodiversity with fewer species, reduced community diversity, and a consistent trophic shift in algal communities (dominance) across all lakes, demonstrated by increasing chlorophyll a (Chl a ). Arnott et al (2022) were unable to link sensitivity of zooplankton communities (i.e., intraspecific variation in community‐level salt responses) to their original species pool or local environmental conditions. Yet, some lakes had more robust zooplankton community responses, possibly due to evolutionary adaptation (Moffett et al 2020).…”
Section: State Of the Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Vitally, Hébert et al (2022) showed that the loss in abundance was accompanied by a loss in zooplankton biodiversity with fewer species, reduced community diversity, and a consistent trophic shift in algal communities (dominance) across all lakes, demonstrated by increasing chlorophyll a (Chl a ). Arnott et al (2022) were unable to link sensitivity of zooplankton communities (i.e., intraspecific variation in community‐level salt responses) to their original species pool or local environmental conditions. Yet, some lakes had more robust zooplankton community responses, possibly due to evolutionary adaptation (Moffett et al 2020).…”
Section: State Of the Sciencementioning
confidence: 99%
“…We know that species occur within communities and ecosystems, and that the interaction between them can modulate the sensitivity of individual species to stressors (Baillard et al 2020; Thompson et al 2021). Kefford et al (2021) and Arnott et al (2022) call for more community‐based toxicity tests and coordinated mesocosm studies that account for species interactions rather than single species toxicity tests performed in laboratories when salinity standards for the protection of aquatic ecosystems are developed. Results reported in this SI provide new knowledge about how lake and coastal ecosystems, zooplankton, plankton and microbial (algal, bacterial, and fungal) communities will likely respond to increasing salinity, not only with reductions in zooplankton abundance, but also with fewer species of zooplankton, and a consistent trophic shift towards primary producers and microbiota.…”
Section: State Of the Sciencementioning
confidence: 99%
“…This is consistent with results that found that Daphnia and other cladocerans in Precambrian Shield lakes (that typically have low ion concentrations and low algae concentrations) are sensitive to chloride at concentrations below current Canadian water quality guidelines (Arnott et al, 2020). There is also some evidence that the local community composition, that is, species interactions, can influence macroinvertebrate and zooplankton species responses to increased salinity (Arnott et al, 2022; Bray et al, 2019).…”
Section: Biological Effectsmentioning
confidence: 99%
“…For example, the chronic guideline for chloride in Canada is based on 28 species, but this is a small subset of the species that live in freshwater habitats. Within a species, few populations are tested, which fails to capture geographical variation in sensitivity (Arnott et al, 2022), that could arise from acclimation, plasticity, evolutionary change, or environmental context. Toxicity tests are typically conducted under ideal temperature and food conditions, and often do not consider the influence of environmental context, such as the influence of potentially modifying ions, food quantity and quality, or the presence of other stressors, including predators (Hintz & Relyea, 2017; Liu & Steiner, 2017).…”
Section: Regulatory Guidelinesmentioning
confidence: 99%
“…SM : The main finding across mesocosms was a 50% decline in zooplankton abundance, which also led to shifts in the communities, increases in algal communities, and a decrease in overall diversity (Hébert et al 2023). Arnott et al (2023) looked at intraspecific variation and found that the same species will have a different response to salt between lakes. We wanted to explain and predict that variation using environmental factors, but it was not explained by anything other than the community itself.…”
mentioning
confidence: 99%